Scaling Existing Lock-based Applications with Lock Elision. - KLEEN, ANDI (Communications of the ACM, 2014)
The article considers scalability of multiuser computer systems which have lock-based computer programs which synchronize data shared between users. The difficulties of high-performance synchronization are acknowledged. Lock elision, an algorithm in which lock-based programs are executed on a lockless fast path under a cache-coherence protocol, is examined, particularly Transactional Synchronization Extensions (TSX) and Restricted Transactional Memory (RTM), computer software created by high technology industries firm Intel Corp. for lock elision.